IMF programmes in developing countries : design and impact - Killick, Tony. (London ; New York : Routledge, 1995)
As linchpin of the global financial system, the International Monetary Fund provides balance of payments support, chiefly to developing countries, conditional on strict remedial policy measures. Its approach to policy remains highly controversial, however. While the Fund claims it has adapted, critics allege its policies are harshly doctrinaire, imposing hardships on already poor people. For the critics, the half-century of its existence is 'fifty years too long' and radical change is essential. This book examines the arguments, tracing the extent of Fund adaptation, presenting major new evidence on the consequences of Fund programmes, and considering its future role.
1. Starting Points -- 2. Continuity and Change in IMF Programme Design, 1982-92 -- 3. Programme Effects: What can we know? -- 4. Issues in the Design of IMF Programmes -- 5. Conclusion: Is fifty years enough?
Includes bibliographical references (pages 194-202) and index.
Keywords: Fonds monetaire international; International Monetary Fund -- Developing countries; International Monetary Fund; Internationaler Wahrungsfonds; Fonds monetaire international; IMF; Development economics; Development economics; structural adjustment; stabilization; international borrowing; economic aid; terms of aid; economic implication; social implication; political problem; role of IMF; survey; balance of payments; external debt; debt repayment; adjustment assistance; aid financing; statistical table; bibliography